Quantitative Morphometric Analysis of Streams in Extreme Humid Areas: A Case Study of the Um-Mawiong River Basin, Mawsynram, Meghalaya - Lyngdoh, Andy T.G; Ryntathiang, Bring Blessing L (Acta Geographica Debrecina Landscape & Environment series, 2023)
Quantitative morphometric analysis of the drainage system is essential to characterising a watershed, as all the hydrologic and geomorphic processes occur within the watershed. Consequently, this plays a crucial role in understanding the geo-hydrological attributes of a drainage basin to the terrain feature and its ﬂow patterns, thus enabling the estimate of the incidence of inﬁltration and runoff and other related hydrological characteristics of a watershed, which strongly impacts natural resource conservation. The study area selected is the Um-Mawiong River basin in Mawsynram, Meghalaya. The basin shows a dendritic pattern that highlights the homogeneity in the texture of the basin. Results suggest that the stream frequency of the basin is 19.10 km², suggesting a faster surface runoff and less infiltration. In addition, it has an Elongation ratio of 0.75 indicating an elongated basin shape. The current study demonstrates that the implementations of GIS techniques are trustworthy, efficient, and capable of managing extensive databases for managing river basins. The present study tries to analyse the linear, areal and relief aspects of the basin using a GIS environment and manipulated for different calculations. The analysis reveals that the total number of stream segments and length are maximum in first-order streams and decrease as stream order increases. The drainage density exhibits a high degree of positive correlation, i.e., 0.87, with its frequency suggesting an increase in stream population concerning increasing drainage density and vice versa.